Tandem Pauson-Khand Reaction Using Carbon Dioxide as the C1-Source - Shyshkanov, Serhii; Vasilyev, Dmitry; Abhyankar, Kedar A.; Stylianou, Kyriakos C.; Dyson, Paul J. (European Journal of Inorganic Chemistry, 2022)
We describe the use of CO2 as a promising C1 source instead of CO in the tandem Pauson-Khand reaction. The reaction is achieved by combining the reduction of CO2 to CO using a metal organic framework (MOF) catalyst with homogeneous rhodium catalysts for the cycloaddition step. A range of substrates were converted in moderate to good yields.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Activation of carbon dioxide; Carbon dioxide reduction; Cascade process; Metal organic frameworks; Pauson-Khand reaction